The Use of Social Media in Restaurants : The Case of Lisbon - Leão, Marta; Karlíček, Miroslav, 1979-; Tahal, Radek, 1970-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
This thesis aims at finding the best practices for implementing an effective social media marketing strategy for small to medium size restaurants, which potential barriers can arise, and which performance measures should be used to identify the influence of social media marketing actions on the business. The author conducted 12 in-depth interviews with restaurant managers, social media experts working in the restaurant field, and restaurant customers. The study focused on the context of Lisbon, Portugal. Among the best practices mentioned by the experts and customers interviewed, the author discovered that the platform TheFork is given substantial importance in the region, that organic and “human-oriented” content seems to bring the most engagement to the participants’ social media efforts, that there has been identified a divergence in thoughts towards influencer marketing between the industry experts and restaurant customers, and that, considering the specific landscape of the studied region, the most common barriers to the implementation of a social media marketing strategy are lack of financial resources and knowledge and the difficulty in differentiating among the competition.
Vedoucí práce: Miroslav Karlíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses